Vindhya Pradesh Second Five Year Plan Revised Volume I - Planning Commission (Planning Commission, 1959)
The Department was fully re-organised during the first five year plan period with the result that handicaps in the initial stages of execution of the Second Five Year Plan have greatly been minimised and the Department is in a position to undertake the execution of an ambitious Second Five Year Plan with facility.
Second Five Year Plan Revised Volume I
Government of India Planning Commission
Keywords: Town Compost Scheme; Plant Protection; Tractor Unit; Crop Competetion; Development of Horticulture; Installation of Rahats; Construction of new wells; Green Manuring; Ghee testing labratory